2014
DOI: 10.1016/j.bmc.2014.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and antimalarial activity of metal complexes of cross-bridged tetraazamacrocyclic ligands

Abstract: Using transition metals such as manganese(II), iron(II), cobalt(II), nickel(II), copper(II), and zinc(II), several new metal complexes of cross-bridged tetraazamacrocyclic chelators namely, cyclen- and cyclam-analogs with benzyl groups, were synthesized and screened for in vitro antimalarial activity against chloroquine-resistant (W2) and chloroquine-sensitive (D6) strains of Plasmodium falciparum. The metal-free chelators tested showed little or no antimalarial activity. All the metal complexes of the dibenzy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
50
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 70 publications
(50 citation statements)
references
References 58 publications
0
50
0
Order By: Relevance
“…These macrocycles can be easily N-functionalized with various groups, allowing the preparation of a wide range of ligands suitable for important applications such as for catalysis [4,8], and the development of metal-based imaging and therapeutic agents in medicine [10].…”
Section: Introductionmentioning
confidence: 99%
“…These macrocycles can be easily N-functionalized with various groups, allowing the preparation of a wide range of ligands suitable for important applications such as for catalysis [4,8], and the development of metal-based imaging and therapeutic agents in medicine [10].…”
Section: Introductionmentioning
confidence: 99%
“…[21] Manganese complexes of cross-bridged tetraazamacrocyclic ligands are highly potent against P. Falciparum strains resistant to chloroquine. [22] A number of zinc complexes with ligands such as quinine and arginine have displayed unique activity against iRBCs. [23, 24] One complex in particular, zinc-desferrioxamine, was found to be more permeative into iRBCs than the desferrioxamine ligand alone as the former exchanges its bound zinc for ferric ions which enhanced uptake.…”
Section: Introductionmentioning
confidence: 99%
“…[1] Depending on the chelated metal, tetraazamacrocyclic complexes have found use in a range of applications, including medical imaging, [2] [3] [4] [5] protein binding agents, [6] [7] and as anti-malarial drugs. [8] [9] Recently we have been interested in the use of this complex type as oxidation catalysts. [10] [11] [12] A recent papers by Que, et al, has shown that addition of a pyridyl pendant arm to a tetraazamacrocycle can result in new and improved oxidation catalysis.…”
Section: Introductionmentioning
confidence: 99%